Simulation with debriefing with video in the teaching of the respiratory physical examination: Satisfaction and self-confidence of nursing students (Research, Society and Development, 2021)
Objective: To evaluate the satisfaction and self-confidence in the learning of nursing students who were part of an experimental class on teaching the respiratory physical examination, based on simulation with video debriefing.   Method: This is an analytical-descriptive and quantitative study, conducted with a sample of 33 undergraduate nursing students from the Federal University of Uberlândia who participated in the experiential class based on simulation and using a video in the debriefing. Data collection was performed by applying the Student Satisfaction and Self-Confidence in Learning (SSSCL) scale to students after participation in the class. Results: There was a predominance of females in the sample with 78.8% and young students with a mean age of 20.91 years. Regarding the satisfaction and self-confidence scale, averages of 4.36 and 4.15, respectively; all items of the scale obtained an average above four, except for item six, with an average of 3.39, even so, a value above the moderate. Female students had lower satisfaction (Bi = -0.451; p  < 0.05), when compared to male students. Self-confidence, on the other hand, did not depend on the profile of the students.  Conclusion: It is concluded that the use of simulation with the use of video in the debriefing promotes satisfaction and self-confidence in learning among nursing students.